Emotions in the Teaching/Learning Process - Shmavonyan, Gayane; Karapetyan, Lili (Armenian Folia Anglistika, 2012)
Emotions play a great role in our daily life, as well as in the teaching process which is closely connected with the emotional sphere of life since teaching is an emotional practice involving emotional understanding, as well as emotional labor. Being in the center of the teaching process, emotions should be paid due attention to in the language classroom since they lead to a better understanding of classroom interactions and more satisfying educational experiences for both language teachers and students. The paper explores the role and significance of students’ and teachers’ emotions in language teaching and learning, as well as the emotional factors that influence the teaching/learning process. It also suggests some strategies for enhancing positive emotions.